Glucocorticoid-Driven NLRP3 Inflammasome Activation in Hippocampal Microglia Mediates Chronic Stress-Induced Depressive-Like Behaviors - Feng, Xiujing; Zhao, Yuan; Yang, Tianyuan; Song, Manyu; Wang, Chaoran; Yao, Yujie; Fan, Honggang (Frontiers in Molecular Neuroscience, 2019)
Chronic stress is a key risk factor for depression, and microglia have been implicated in the pathogenesis of the disease. Recent studies show that the Nod-like receptor protein 3 (NLRP3) inflammasome is expressed in microglia and may play a crucial role in depression. However, the mechanism of NLRP3 inflammasome activation in hippocampal microglia and its role in depressive-like behaviors remain poorly understood. In this study, rats were subjected to 6 h of restraint stress per day for 21 days to produce a model of stress-induced depression. Behavioral tests and serum corticosterone were used to assess the success of the model. Furthermore, HAPI cells were pretreated with dexamethasone (5 × 10-7 M) to assess stress-induced changes in microglial cells in culture. The microglial marker Iba-1, reactive oxygen species (ROS), nuclear factor kappa B (NF-κB) and key components of the NLRP3 inflammasome and its downstream inflammatory effectors (IL-1β and IL-18) were measured. Chronic stress induced depressive-like behavior, increased serum corticosterone levels and produced hippocampal structural changes. Chronic stress and dexamethasone both increased Iba-1 expression and ROS formation and also elevated levels of NF-κB, NLRP3, cleaved caspase-1, IL-1β and IL-18. After use of the NF-κB inhibitor BAY 117082 and knocked out NLRP3 in vitro decreased ROS formation and the expression of Iba-1, NF-κB and NLRP3 as well as levels of cleaved caspase-1, IL-1β and IL-18. These findings suggest that activation of the glucocorticoid receptor-NF-κB-NLRP3 pathway in hippocampal microglia mediates chronic stress-induced hippocampal neuroinflammation and depression-like behavior.